Smart Contracts and Their Implications for Conventional Contract Law - Hendri Khuan; Yenni Novita Wulandari; Chak Sothy (Rechtsnormen: Journal of Law, 2025)
Background. The rise of blockchain technology has led to the development of smart contracts, which are self-executing contracts with the terms of the agreement directly written into code. While they promise enhanced efficiency, security, and automation, the legal implications of smart contracts on conventional contract law remain largely underexplored. The advent of these digital contracts challenges traditional legal frameworks and calls for a reassessment of existing contract law principles. Objective. This study aims to analyze the implications of smart contracts for conventional contract law, focusing on the legal, ethical, and practical challenges they present. The research seeks to evaluate how smart contracts align with or diverge from traditional contract principles such as offer, acceptance, and enforceability. Method. A qualitative research approach was employed, utilizing a comprehensive literature review and case law analysis to explore the intersection of smart contracts and conventional contract law. Interviews with legal experts and blockchain developers were also conducted to gather insights on real-world applications. Results. The findings reveal that while smart contracts offer substantial benefits in terms of automation and security, they also raise issues related to ambiguity, legal recognition, and the need for updated regulations. The study identifies a gap in existing legal frameworks regarding the enforceability of smart contracts. Conclusion. Smart contracts have significant potential to revolutionize contract law, but their integration into conventional legal systems requires substantial legal reform and adaptation. Further research is needed to establish clear regulatory standards.